2022
DOI: 10.1002/ijfe.2744
|View full text |Cite
|
Sign up to set email alerts
|

Market efficiency of the cryptocurrencies: Some new evidence based on price–volume relationship

Abstract: Cryptocurrencies have emerged as an important investment avenue in the past few years. Investors are increasingly interested in these currencies amid surging financial returns. In this context, understanding market efficiency of cryptocurrency has become very crucial for investors and academicians. The price–volume framework is a popular approach in financial economics to understand the market efficiency of stocks in the stock markets. Therefore, this article examines the market efficiency of cryptocurrencies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…Tese fndings imply that the dominant direction of the information fow is from volume changes to returns. Tis result difers from the dominant direction found in the Bitcoin spot market by Sahoo and Sethi [5,56]. Sahoo found that returns Granger caused volumes but not vice versa [5].…”
Section: Resultsmentioning
confidence: 83%
See 3 more Smart Citations
“…Tese fndings imply that the dominant direction of the information fow is from volume changes to returns. Tis result difers from the dominant direction found in the Bitcoin spot market by Sahoo and Sethi [5,56]. Sahoo found that returns Granger caused volumes but not vice versa [5].…”
Section: Resultsmentioning
confidence: 83%
“…Tis result difers from the dominant direction found in the Bitcoin spot market by Sahoo and Sethi [5,56]. Sahoo found that returns Granger caused volumes but not vice versa [5]. Fousekis and Tzaferi found that spillover from returns to volumes was stronger than that in the opposite direction [56].…”
Section: Resultsmentioning
confidence: 85%
See 2 more Smart Citations
“…Although numerous systematic literature reviews have been published on various aspects of digital payments, the literature review presented in this paper is deliberately brief (Sahoo and Sethi, 2022).…”
Section: Methodsmentioning
confidence: 99%